The paradox of pedagogy transposition: Learning from inhibitors to teacher change: Lessons from a Zimbabwean research project in environmental education - Kathy Stiles (Environmental Association of Southern Africa, 1995)
Definition of paradox used in this paper is "a person or thing conflicting with a preconceived notion of what is reasonable or possible" (Allen 1990:862). A belief that a pedagogy developed and proven in one context may generalize or exist comfortably in other contexts, may have a base in a simplistic view of the importance of teaching and learning environments. A case study of transposition of a Northern pedagogy to rural Zimbabwean teachers questions the preconceived notion that such transposition was possible or appropriate within the new context. Further, paradox can be observed in the facilitation process itself.